Mechanical Evaluation of Long Titanium Alloy Clip—Comparison of Cobalt Alloy Clip - HORIUCHI, Tetsuyoshi (Neurol Med Chir (Tokyo), 2014)
Long titanium aneurysm clips have recently been released. In the present study, comparative study of long titanium and cobalt alloy clips was performed. Two kinds of Sugita long clips (straight clips of 25- and 35-mm blade length) made of titanium and cobalt alloys were tested by measuring the closing force, the anti-scissoring torque, and the maximum opening width. There were some differences between the two materials. In the 25-mm blade length clip, closing force and maximum opening width of titanium alloy clip were greater than those of cobalt alloy clip. By contrast, the anti-scissoring torque of 35-mm blade length titanium clip was stronger than that of the cobalt. The long titanium clips would have equivalent endurance to long cobalt clip and are safe for clinical use.